PRINSIP EVIDENCE BASED POLICY MAKING DALAM KONTEKS AUDIT PENDAHULUAN OPERASIONAL BPJS KESEHATAN - Maria Gabby (Conference In Business, Accounting, And Management (CBAM), 2015)
The National Health Insurance Scheme (JKN) organized by the Social Security Agency (BPJS) Health has begun to be implemented from 1 January 2014.Implementasi National Health Insurance Program in Indonesia found the problem. Operational hierarchy starting from primary health care such as health centers to referral health services such as hospitals need to be addressed in a professional manner. Flow of funds before the transition Jamsostek be BPJS Employment and PT Askes be BPJS be audited Audit Agency (BPK) .They hope BPJS to return to khittah, which provide protection and social welfare for the people, as the mandate of Law 24 of 2011 on BPJS. The paper needs to be done in order to ensure that operational processes BPJS accordance with regulatory standards and policies as well as the management of the resources that the state assets in the process runs effectively and efficiently. Step is carried out by the operational audit. Operational audit BPJS is expected to identify activities, programs, and activities that standards are still in need of repair. Operational audits BPJS produce recommendations on the improvement of the implementation of various programs and activities with the standard application of the BPJS. BPJS standard application is an attempt to realize a concept JKN that can meet real and optimal public health insurance since its launch stages of planning to operational implementation. Â Keywords: Operational audit, BPJS